Protective Effect of Focal Adhesion Kinase against Skeletal Muscle Reperfusion Injury after Acute Limb Ischemia. Issue 3 (March 2015) - Flück, M.; von Allmen, R.S.; Ferrié, C.; Tevaearai, H.; Dick, F.
Abstract : Objectives: In cardiac muscle, ischemia reperfusion (IR) injury is attenuated by mitochondrial function, which may be upregulated by focal adhesion kinase (FAK). The aim of this study was to determine whether increased FAK levels reduced rhabdomyolysis in skeletal muscle too. Material and methods: In a translational in vivo experiment, rat lower limbs were subjected to 4 hours of ischemia followed by 24 or 72 hours of reperfusion. FAK expression was stimulated 7 days before (via somatic transfection with pCMV-driven FAK expression plasmid) and outcomes were measured against non-transfected and empty transfected controls. Slow oxidative (i.e., mitochondria-rich) and fast glycolytic (i.e., mitochondria-poor) type muscles were analyzed separately regarding rhabdomyolysis, apoptosis, and inflammation. Severity of IR injury was assessed using paired non-ischemic controls. Results: After 24 hours of reperfusion, marked rhabdomyolysis was found in non-transfected and empty plasmid-transfected fast-type glycolytic muscle, tibialis anterior. Prior transfection enhanced FAK concentration significantly ( p = 0.01). Concomitantly, levels of BAX, promoting mitochondrial transition pores, were reduced sixfold ( p = 0.02) together with a blunted inflammation ( p = 0.01) and reduced rhabdomyolysis ( p = 0.003). Slow oxidative muscle, m. soleus, reacted differently: although apoptosis was detectable after IR, rhabdomyolysis did not appear before 72 hours of reperfusion; and FAK levels were not enhanced in ischemic muscle despite transfection ( p = 0.66). Conclusions: IR-induced skeletal muscle rhabdomyolysis is a fiber type-specific phenomenon that appears to be modulated by mitochondria reserves. Stimulation of FAK may exploit these reserves constituting a potential therapeutic approach to reduce tissue loss following acute limb IR in fast-type muscle.